2009
DOI: 10.1111/j.1365-2869.2009.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of sleepiness indicators to partial sleep deprivation, time of day and time on task in a driving simulator - the DROWSI project

Abstract: SUMMARY Studies of driving and sleepiness indicators have mainly focused on prior sleep reduction. The present study sought to identify sleepiness indicators responsive to several potential regulators of sleepiness: sleep loss, time of day (TOD) and time on task (TOT) during simulator driving. Thirteen subjects drove a high-fidelity moving base simulator in six 1-h sessions across a 24-h period, after normal sleep duration (8 h) and after partial sleep deprivation (PSD; 4 h). The results showed clear main effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 49 publications
7
85
2
3
Order By: Relevance
“…Nevertheless, the present study revealed that, for the studied drivers, falling asleep and feeling sleepiness while driving were associated with both loud snoring or apnea and short sleep duration, similar to results found in Western countries (1)(2)(3)(4)(5)9). Feeling subjective sleepiness while driving is coincident with deteriorated performance in driving simulator tasks and real driving situations (26)(27)(28). Moreover, the existence of subjective sleepiness clearly raises the risk of MVCs (6-8, 12).…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, the present study revealed that, for the studied drivers, falling asleep and feeling sleepiness while driving were associated with both loud snoring or apnea and short sleep duration, similar to results found in Western countries (1)(2)(3)(4)(5)9). Feeling subjective sleepiness while driving is coincident with deteriorated performance in driving simulator tasks and real driving situations (26)(27)(28). Moreover, the existence of subjective sleepiness clearly raises the risk of MVCs (6-8, 12).…”
Section: Discussionsupporting
confidence: 84%
“…KSS increased with time on task and blink duration was longer with time on task, this is in line with earlier research [34,35]. Our results indicate that future development and improvements of driver support systems may use different criteria's or thresholds for activations of warnings day time compare to night time if the aim is to avoid critical situations.…”
Section: Discussionsupporting
confidence: 80%
“…However, none of the participants in our study required prescription lenses. The system provides 13 ocular measures sampled each minute, of which the following were selected based on previous work [21][22][23][24][25][26][27] (detailed description of each measure provided in Table 1): positive and negative amplitude/velocity ratio of each blink (PosAVR, NegAVR), Johns Drowsiness Scale (JDS) score, the percentage of time with eyes closed (%TEC), and mean blink total durations (BTD). For all measures, higher values indicate higher levels of sleepiness.…”
Section: Infrared Oculographymentioning
confidence: 99%